Successful conversion surgery after comprehensive therapy in a patient with MSI-H but pMMR metastatic gastric mixed adenoneuroendocrine carcinoma: a case report and literature review - He, Jun; Wang, Li; Tuo, Chuanlei; Gong, Weihua; Liu, Yong (Frontiers in Oncology, 2024)
Gastric mixed adenoneuroendocrine carcinoma (MANEC) is a rare and highly aggressive malignancy characterized by both exocrine and neuroendocrine components. Treatment options for metastatic cases are limited, with typical therapeutic approaches involving a combination of chemotherapy and immunotherapy. A 68-year-old male with metastatic gastric MANEC was treated with targeted therapy, immunotherapy, and chemotherapy, including S-1, apatinib, cadonilimab, and paclitaxel. After six cycles, the liver metastases resolved completely, and the primary tumor achieved partial remission, leading to conversion surgery. The patient underwent a radical D2 gastrectomy with R0 resection, including proximal gastrectomy, splenectomy, omentectomy, and esophagogastric anastomosis, along with radiofrequency ablation of liver metastases. Postoperative pathology confirmed the disappearance of liver metastases but revealed residual adenocarcinoma in the primary gastric lesion and neuroendocrine components in the perigastric lymph nodes. The patient was discharged seven days post-surgery. Five months postoperatively, new liver metastases were detected, exhibiting neuroendocrine differentiation. The patient was subsequently treated with a maintenance regimen of S-1 and pembrolizumab. This case highlights the significant heterogeneity of gastric MANEC and the challenges in managing such cases. While conversion surgery can be effective in certain contexts, the high likelihood of postoperative recurrence and metastasis, particularly in neuroendocrine components, necessitates cautious consideration. Further research is needed to evaluate the long-term benefits of conversion surgery in metastatic gastric MANEC and to develop tailored therapeutic strategies.